Measurement of biomarkers in surveys in developing countries: opportunities and problems - Boerma, T.; Holt, E.; Black, R.
tbls.
pp. 303-314
Keywords: Salud Publica; Enfermedades; Mortalidad; Tecnicas Demograficas